Editorial Vol.4 - Bajracharya, Ramesh Kumar (Journal of Tourism and Himalayan Adventures, 2022)
The scholars were NMA’s first batch (2021) research grant recipients who had carried out their 2500 m. and above field-based studies on the topics like mountain sciences, mountaineering and trekking tourism, adventure tourism, and the Himalayan cultural heritages